2016
DOI: 10.3892/mmr.2016.5506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microRNA-338-3p on morphine-induced apoptosis and its underlying mechanisms

Abstract: The aim of the present study was to investigate the effects of microRNA-338-3p (miR-338-3p) on morphine (MP)-induced apoptosis, and its underlying mechanisms. Freshly‑isolated mouse peritoneal macrophages were cultured in vitro and treated with MP following transfection with miR‑338‑3p mimic, inhibitor or controls. miR‑338‑3p expression levels increased significantly following MP treatment (P<0.01). This increase was enhanced following transfection with miR‑338‑3p mimic (P<0.05) and abrogated following transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…[20][21][22][23][24][25][26] Recently, it was shown that miR-338 also played important roles in cell apoptosis, differentiation and polarity in noncancerous cells during some pathological processes, and overexpression of miR-338 has been shown to have therapeutic effect on nervous diseases and osteoporosis. [27][28][29] In current study, we found that miR-338 had a suppressive effect on A/R-induced hypernomic autophagy and autophagic cell death in cardiomyocytes, suggesting a potential therapeutic effect of miR-338 on ischemic cardiovascular diseases.…”
Section: Figuresupporting
confidence: 50%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26] Recently, it was shown that miR-338 also played important roles in cell apoptosis, differentiation and polarity in noncancerous cells during some pathological processes, and overexpression of miR-338 has been shown to have therapeutic effect on nervous diseases and osteoporosis. [27][28][29] In current study, we found that miR-338 had a suppressive effect on A/R-induced hypernomic autophagy and autophagic cell death in cardiomyocytes, suggesting a potential therapeutic effect of miR-338 on ischemic cardiovascular diseases.…”
Section: Figuresupporting
confidence: 50%
“…MiR‐338 (miR‐338‐3p) is relatively well characterized tumor suppressor, which was shown to be frequently downregulated in several parenchymal carcinomas, including lung cancer, liver cancer, neuroblastoma, breast cancer, colorectal cancer, esophageal cancer, and gastric cancer . Recently, it was shown that miR‐338 also played important roles in cell apoptosis, differentiation and polarity in non‐cancerous cells during some pathological processes, and overexpression of miR‐338 has been shown to have therapeutic effect on nervous diseases and osteoporosis . In current study, we found that miR‐338 had a suppressive effect on A/R‐induced hypernomic autophagy and autophagic cell death in cardiomyocytes, suggesting a potential therapeutic effect of miR‐338 on ischemic cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 63%
“…It has been reported that SOX4 may interact with many signaling pathways, such as Wnt (8) or p53 (18), to influence cellular apoptosis. Low SOX4 expression can also facilitate peritoneal macrophage apoptosis by activating caspase-3 (19). Hur et al demonstrated that there is an important structural domain in SOX4 related to apoptosis; when the glycine in the domain is replaced by serine, apoptosis is inhibited (20).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing pain relief, morphine has also been reported to modulate apoptosis in various types of cells, including immune, neuronal and cancer cells, suggested its potential effects on immunomodulation, nerve damage and tumor progression (2)(3)(4). Although opioid receptors are essential for opioid-induced effects, an increasing number of studies have demonstrated that other mechanisms beyond opioid receptors may be involved in morphine-mediated cell apoptosis (5)(6)(7). However, the underlying molecular mechanisms remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%